Trends in smoking and quitting in China from 1993 to 2003: National Health Service Survey data - Qian, Juncheng (World Health Organization, 2010)
OBJECTIVE: China has about 350 million smokers, more commonly men. Using data from National Health Service Surveys conducted in 1993, 1998 and 2003, we (i) estimated trends in smoking prevalence and cessation according to sociodemographic variables and (ii) analysed cessation rates, quitting intentions, reasons for quitting and reasons for relapsing. METHODS: Data were collected from approximately 57 000 households and 200 000 individuals in each survey year. Household members > 15 years of age were interviewed about their smoking habits, quitting intentions and attitudes towards smoking. We present descriptive data stratified by age, sex, income level and rural versus urban residence. FINDINGS: In China, current smoking in those > 15 years old declined 60–49% in men and 5–3.2% in women over 1993–2003. The decline was more marked in urban areas. However, heavy smoking (≥ 20 cigarettes daily) increased substantially overall and doubled in men. The average age of uptake also dropped by about 3 years. In 2003, 7.9% of smokers reported intending to quit, and 6% of people who had ever smoked reported having quit. Of former smokers, 40.6% quit because of illness, 26.9% to prevent disease and 10.9% for financial reasons. CONCLUSION: Smoking prevalence declined in China over the study period, perhaps due to the combined effect of smoking cessation, reduced uptake in women and selective mortality among men over 40 years of age. However, heavy smoking increased. People in China rarely quit or intend to quit smoking, except at older ages. Further tobacco control efforts are urgently needed, especially in rural areas.